2019
DOI: 10.1111/mmi.14198
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic developmental regulator MciZ targets FtsZ across Bacillus species and inhibits bacterial division

Abstract: Summary Cell division in most bacteria is directed by FtsZ, a conserved tubulin‐like GTPase that assembles forming the cytokinetic Z‐ring and constitutes a target for the discovery of new antibiotics. The developmental regulator MciZ, a 40‐amino acid peptide endogenously produced during Bacillus subtilis sporulation, halts cytokinesis in the mother cell by inhibiting FtsZ. The crystal structure of a FtsZ:MciZ complex revealed that bound MciZ extends the C‐terminal β‐sheet of FtsZ blocking its assembly interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…It provides a solid starting point to robotic high‐throughput screening for high‐affinity inhibitors targeting the GTP‐binding site of Gram‐positive S. aureus FtsZ. Fluorescence and ITC binding measurements should be combined with phenotypically characterizing inhibitor effects on bacterial division . On the other hand, very high‐affinity ligands, binding to the GTP or other site, may induce apo‐SaFtsZ T folding in the absence of osmolytes, so that they could be picked up by an appropriate fluorescence thermal shift screen designed to detect apo‐SaFtsZ T stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…It provides a solid starting point to robotic high‐throughput screening for high‐affinity inhibitors targeting the GTP‐binding site of Gram‐positive S. aureus FtsZ. Fluorescence and ITC binding measurements should be combined with phenotypically characterizing inhibitor effects on bacterial division . On the other hand, very high‐affinity ligands, binding to the GTP or other site, may induce apo‐SaFtsZ T folding in the absence of osmolytes, so that they could be picked up by an appropriate fluorescence thermal shift screen designed to detect apo‐SaFtsZ T stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…However, MciZ does not bind to the IDC either, and instead interacts with H10 and beta strand 9 of FtsZ. This results in occlusion of subunit-subunit contacts that causes capping of the growing FtsZ protofilament end ( Araujo-Bazan et al, 2019 ). Other peptide inhibitors of FtsZ, including Kil from bacteriophage lambda and GP0.4 from bacteriophage T7, disrupt assembly of Ec FtsZ protofilaments, but their binding sites on FtsZ are not yet known ( Kiro et al, 2013 ; Haeusser et al, 2014 ; Hernandez-Rocamora et al, 2015 ).…”
Section: Small Inhibitory Peptides That Bind Near the Idcmentioning
confidence: 99%
“…Moreover, it can also cause filamentation in vitro. A recent study showed that MciZ can affect B. subtilis sporulation: Excessive amounts of MciZ produced intracellularly or added exogenously can not only decrease spore formation efficiency but also inhibit spore germination (Araújo-Bazán et al, 2019).…”
Section: Mciz Regulates Cell Divisionmentioning
confidence: 99%